2005
DOI: 10.1152/ajpregu.00809.2004
|View full text |Cite
|
Sign up to set email alerts
|

CCK enhances response to gastric distension by acting on capsaicin-insensitive vagal afferents

Abstract: . CCK enhances response to gastric distension by acting on capsaicin-insensitive vagal afferents. Am J Physiol Regul Integr Comp Physiol 289: R695-R703, 2005. First published May 19, 2005 doi:10.1152/ajpregu.00809.2004.-Capsaicin treatment destroys vagal afferent C fibers and markedly attenuates reduction of food intake and induction of hindbrain Fos expression by CCK. However, both anatomical and electrophysiological data indicate that some gastric vagal afferents are not destroyed by capsaicin. Because CCK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Sham-vagotomized control rats (n ϭ 8) were prepared by surgically approaching the vagi, but not sectioning them. These procedures have previously been described in detail (42,48). Briefly, rats were anesthetized with a mixture containing ketamine (50 mg/kg), acepromazine (2 mg/kg), and xylazine (25 mg/kg) (0.1 ml mixture/100 g body wt).…”
Section: Surgeries and Capsaicin Treatmentmentioning
confidence: 99%
“…Sham-vagotomized control rats (n ϭ 8) were prepared by surgically approaching the vagi, but not sectioning them. These procedures have previously been described in detail (42,48). Briefly, rats were anesthetized with a mixture containing ketamine (50 mg/kg), acepromazine (2 mg/kg), and xylazine (25 mg/kg) (0.1 ml mixture/100 g body wt).…”
Section: Surgeries and Capsaicin Treatmentmentioning
confidence: 99%
“…Recently, van De Wall et al (47) reported that lorglumide did not diminish the expression of Fos induced by 2-ml distension; however, it completely reversed the enhancement of distension-induced Fos expression by CCK. This suggests that lorglumide specifically reduces the response of vagal afferents to distension.…”
Section: Discussionmentioning
confidence: 97%
“…Our final experiment addressed whether the diminished feeding response to gastric distension in OLETF rats could be explained, at least partially, through decreased vagal activation of distension signals. Gastric distension induces Fos within the NTS region of the DVC (19,47), an area established as the primary termination site for vagal afferent input from the stomach (50). Furthermore, distension-induced Fos expression in the NTS is abolished via vagotomy (21,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCK also increases satiation via CCK-A receptors on vagal afferents which signal via the nucleus of the solitary tract (NTS) in the brainstem (van de Wall et al, 2005). LCFAs also stimulate the release of the anorectic gut hormones peptide YY (PYY) and glucagon-like peptide-1 (GLP-1) from human enteroendocrine cells (Stoeckel et al, 2008).…”
Section: Lipid Sensingmentioning
confidence: 99%